Chemistry of pyrotechnics basic principles and theory - Conkling, John A., 1943-; Mocella, Chris (Boca Raton, Fla. : CRC Press, 2011)
"Chemistry of Pyrotechnics: Second Edition is simply the most definitive reference in this field. Author J.A. Conkling covers the requisite background in chemistry, thermodynamics, and light emission; introduces oxidizing agents, fuels, binders, and retardants; and then explores virtually every aspect of formulating pyrotechnics. Topics include the requirements for and preparation of high-energy mixtures, ignition and propagation, heat and delay compositions, and color and light production, including sparks, flitter, and glitter"--
ch. 1. Introduction -- ch. 2. Basic chemical principles -- ch. 3. Components of high-energy mixtures -- ch. 4. Pyrotechnic principles -- ch. 5. Ignition and propagation -- ch. 6. Sensitivity -- ch. 7. Heat compositions : ignition mixes, delays, thermites, and propellants -- ch. 8. Color and light production -- ch. 9. Smoke and sound.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Fireworks; Electronic books